2020
DOI: 10.1097/md.0000000000020957
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of primary malignant melanoma of the esophagus

Abstract: Primary malignant melanoma of esophagus (PMME) is a rare malignant tumor of esophagus. This study aimed to investigate the clinic pathologic characteristics and analyze the factors that might affect the prognosis of PMME patients. A total of 20 PMME patients who underwent surgical treatment in our hospital from 1975 to 2017 were analyzed. The clinical data, surgical and pathologic features of all patients were collected. For 20 PMME patients, the average age was 57.3 ± 10.7 years, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
3
15
0
1
Order By: Relevance
“…Even if the endoscopic biopsy was used, the preoperative diagnostic accuracy of PMME was only about 80% [ 4 ]. Sometimes the histological diagnosis of PMME can be challenging for several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if the endoscopic biopsy was used, the preoperative diagnostic accuracy of PMME was only about 80% [ 4 ]. Sometimes the histological diagnosis of PMME can be challenging for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment method of PMME is radical resection of tumor. Chen et al found that early detection of the disease and radical resection of the tumor were critical for better survival of the PMME patients [ 4 ]. However, the risk recurrence is extremely high after an initial staging operation, and the interval between primary surgery and recurrence was only 4.5 months [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…По данным T. Oshiro и соавт., развитие МП ассоциируется с хроническим эзофагитом, гиперпластическими изменениями и акантозом [16]. Так, установлено, что под действием кислого рефлюкса при гастроэзофагеальной рефлюксной болезни хроническое воспаление слизистой пищевода и гиперпластические изменения приводили к распространению меланоза, а соответственно и риску прогрессирования до ПМП [17].…”
Section: этиология и теории патогенеза пмпunclassified
“…About 18.4% of PMME patients present with metastatic disease at the time of diagnosis and 89.7% develop recurrence or metastasis within a few months from diagnosis [1] . As a result, PMME tends to have a poor 5-year overall survival (OS) ranging between 4% to 37.5% [1] , [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%